2016
DOI: 10.1590/0103-9016-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Yield-scaled global warming potential of two irrigation management systems in a highly productive rice system

Abstract: , 55 % lower compared to CF30, while no differences in nitrous oxide emissions were observed between treatments (p > 0.05). No yield differences between irrigation systems were observed in two of the rice seasons (p > 0.05) while AWDI promoted yield reduction in one of the seasons (p < 0.05). When rice yield and greenhouse gases (GHG) emissions were considered together, the AWDI irrigation system allowed for lower yield-scaled total global warming potential (GWP). Higher irrigation water productivity was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
(22 reference statements)
3
34
1
1
Order By: Relevance
“…The authors explained that a positive GHGI value is indicative of a net source of CO 2 equivalent per kg of yield whilst a negative value indicates a net sink of GHG to the soil. GWPY studies have been conducted for rice cultivation systems and other arable cropping systems in various countries [17][18][19][20], but literature on such studies in Ghana and African rice cultivation systems is rare. For Ghana, the lack of adequate investments in the agricultural sector and the high percentage of smallholders who still employ rudimentary farming practices make it imperative for efficient farming systems which encourage optimal use of inputs to be developed.…”
Section: Yield-scaled Global Warming Potential (Greenhouse Gas Intensmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors explained that a positive GHGI value is indicative of a net source of CO 2 equivalent per kg of yield whilst a negative value indicates a net sink of GHG to the soil. GWPY studies have been conducted for rice cultivation systems and other arable cropping systems in various countries [17][18][19][20], but literature on such studies in Ghana and African rice cultivation systems is rare. For Ghana, the lack of adequate investments in the agricultural sector and the high percentage of smallholders who still employ rudimentary farming practices make it imperative for efficient farming systems which encourage optimal use of inputs to be developed.…”
Section: Yield-scaled Global Warming Potential (Greenhouse Gas Intensmentioning
confidence: 99%
“…Tarlera et al [19] also studied how water management impacts both CH 4 and N 2 O emissions from rice paddies under two irrigation systems viz conventional water management (continuous flooding) and an alternative system (controlled deficit irrigation allowing for wetting and drying, AWDI). The results of the study showed that the AWDI system emitted 55% less CH 4 emissions compared to the continuous flooding system.…”
Section: Water Management and Research Effortsmentioning
confidence: 99%
“…Previous studies found that AWD reduced water input and kept rice grain yield at normal level (or even increased) because of the enhancement in root growth, grain-filling rate, and remobilization of carbon reserves from vegetative tissues to grains (Yang et al 2007;Zhang et al 2008). Furthermore, while CH 4 emission was reduced by 40-70%, AWD could increase N0 2 emissions from paddy fields in the world (e.g., Wassmann et al 2000;Farooq et al 2009;Pandey et al 2014;Tarlera et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the mean rice yields on the CF30 plots were 11,171, 10,387, and 9803 kg per ha, during each of three crop seasons, while the mean seasonal yields on the AWDI plots were 10,170, 8700, and 8992 kg per ha, respectively [194]. The reductions in the mean yields are statistically significant in years two and three.…”
Section: Intermittent Drainage Vs Continuous Floodingmentioning
confidence: 89%
“…In a three-year experiment conducted in southeastern Uruguay, with an indica rice cultivar, Tarlera et al [194] compared the methane and nitrous oxide emissions on rice fields that were flooded continuously from 30 days after emergence (CF30), with fields that were irrigated intermittently from 30 days after emergence through 70 days after emergence (AWDI). The second set of fields was then flooded continuously for the remainder of the season.…”
Section: Intermittent Drainage Vs Continuous Floodingmentioning
confidence: 99%